2014
DOI: 10.1093/schbul/sbu076
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar-Thalamic Connectivity in Schizophrenia

Abstract: The literature on alterations in brain structure and function in schizophrenia, particularly in relationship to impairments in cognitive, motor, and affective functions, has made it increasingly clear that changes in the function of a single brain region cannot explain the range of impairments seen in this illness. [1][2][3][4] This realization has led to a surgence of interest in studies examining neurobiological changes in schizophrenia from the perspective of brain networks and connections among brain regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 69 publications
2
26
0
1
Order By: Relevance
“…It has been suggested (Ferrarelli et al, ) that impairments in spindle activity in schizophrenia patients and in relatives sharing the genetic background (Manoach et al, ; Schilling et al, ) reflect deficits in thalamic‐reticular and thalamocortical mechanisms (Buchmann et al, ), representing a biological marker of schizophrenia. Functional magnetic resonance imaging (fMRI) resting‐state studies support the notion of functional abnormalities in thalamocortical circuits in schizophrenia (Barch, ), reporting reduced thalamic‐prefrontal cortex connectivity (Anticevic et al, ; Woodward, Karbasforoushan, & Heckers, ) as well as enhanced thalamic‐sensory motor cortices connectivity (Anticevic et al, ; Klingner et al, ; Woodward et al, ), which correlated with symptom severity in a longitudinal fMRI study (Anticevic et al, ). Furthermore, in the longitudinal fMRI resting‐state study, thalamic connectivity abnormalities predated the onset of schizophrenia (Anticevic et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…It has been suggested (Ferrarelli et al, ) that impairments in spindle activity in schizophrenia patients and in relatives sharing the genetic background (Manoach et al, ; Schilling et al, ) reflect deficits in thalamic‐reticular and thalamocortical mechanisms (Buchmann et al, ), representing a biological marker of schizophrenia. Functional magnetic resonance imaging (fMRI) resting‐state studies support the notion of functional abnormalities in thalamocortical circuits in schizophrenia (Barch, ), reporting reduced thalamic‐prefrontal cortex connectivity (Anticevic et al, ; Woodward, Karbasforoushan, & Heckers, ) as well as enhanced thalamic‐sensory motor cortices connectivity (Anticevic et al, ; Klingner et al, ; Woodward et al, ), which correlated with symptom severity in a longitudinal fMRI study (Anticevic et al, ). Furthermore, in the longitudinal fMRI resting‐state study, thalamic connectivity abnormalities predated the onset of schizophrenia (Anticevic et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…Working memory processes encompass the ability to temporarily store and manipulate information “on-line” and given its relationship to the functioning of the dlPFC, is closely linked with executive functioning ability (for review, see Barch & Sheffield, 2014). Due to such reliable impairments in working memory in schizophrenia, five studies assessed its relationship with functional connectivity.…”
Section: Review Of Resting-state Functional Connectivity and Cognimentioning
confidence: 99%
“…In addition, abnormalities in the cerebellum have also been observed in schizophrenia, with evidence of white matter abnormalities within certain cerebellar lobes (Kim et al, 2014), as well as abnormal size and decreased blood flow in the cerebellum during a broad range of cognitive tasks (Andreasen et al, 2008; Barch, 2014). Importantly, reduced functional connectivity between the cerebellum and medial dorsal nucleus of the thalamus has been observed in schizophrenia, providing evidence of abnormalities in this portion of the CCTCC as well (Anticevic et al, 2014; Collin et al, 2011).…”
Section: 1 Cognitive Dysmetria and The Cortico-cerebellar-thalamic-mentioning
confidence: 99%
“…Consistent with the model, the SZ group did not transition to a brain–accuracy network that engaged key subcortical, thalamic, and cerebellar regions as in the high-performing controls with the best working memory capacities. Evidence is accumulating for the thalamus as a key node in this brain–learning network in SZ (54). Studies have demonstrated thalamic hypoconnectivity between frontal and striatal regions and hyperconnectivity in sensory, somatosensory, and motor regions in chronic, early, and at-risk for SZ groups (55–58).…”
Section: Discussionmentioning
confidence: 99%